Penerapan Asuhan Keperawatan Pada Gangguan Sistem Pencernaan “Gastritis” - Suprapto Suprapto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The purpose of applying nursing care by using a nursing process approach with priority problems meeting the basic needs of pain. The research method used with the case study approach is designed descriptively, which in this case study will explain the cases experienced by patients with gastritis. The results of research from the results of case studies that people with gastritis will be worse if he experiences stress. In addition to stress, the entry of air through the mouth when consuming food can also cause an increasingly bloated stomach and increased belching frequency. Conclusions obtained from the main complaints of patients say uluhati like pricked and felt at mealtime or late eating with the nature of complaints disappearing arise. The objective data is that the general condition of the patient is weak, the patient seems to wince The main nursing diagnoses are pain related to gastric mucosal irritation, nutritional changes less than the body's needs related to inadequate intake and the risk of lack of fluid volume associated with nausea and vomiting. In planning the writer involves the family in determining the priority of the problem of choosing the right action in the nursing process of gastritis. Interventions carried out adjusted to interventions contained in the theory. The implementation phase is based on a plan that has been prepared by the author together with the client and family. In evaluating the nursing process in clients with gastritis always refers to the purpose of meeting the needs of the client. The results of the evaluation conducted for three days showed that all problems could be overcome.